Fabrication and NDT of damaged composite materials - Koh, Andrew Kai Loon (2017)
As composites gain popularity in the aviation industry, it is important to further understand the different properties. As it would appear that not much research has been done on the ability of ultrasonic testing to detect physical damages to composite materials. This experiment has two aims. First, to determine the ability of using ultrasonic A-scan to determine the properties of composite materials and the use of ultrasonic C-scan to correctly identify the defects and damage present in them. Second, to create a controlled crack growth of carbon fibre. Three different batches of carbon fibres with defects in them were created and tested. Ultrasonic A and C-scan would be conducted on the specimens, following, mechanical tests such as tensile test and a double cantilever beam test would be conducted on the specimens. After which, Ultrasonic C-scan would be done to determine the ability of detecting delamination of the carbon fibre specimens. To further investigate the capability of the C-scan, a test piece was created to determine if it would be possible to identify regions where only the matrix of the composite material was present. Holes were created on this test piece before placing it into the autoclave. The C-scan was also characterised by showing the effects of using different levels of gains and gate position as well as evaluating the use of the maximum peak method and the rising edge method.